Changing Spaces: Negotiating Representations of Space in England and the New World (c.1607-1642) - O'Malley, Sarah (2019)
This thesis explores how early modern writers, of both literary and non-literary texts, responded to the New World colonial project in their representations of the relationship between subject and space. It argues that the colonial experience fundamentally changed how this relationship was understood, performed, and represented by early modern writers. The spatial turn and the field of Literary Geographies have made significant inroads into early modern literary and cultural studies over recent years. However, there has been very little work undertaken on the reflexive relationship between the production and representation of space in England and its New World colonies – this thesis addresses this gap. I consider three different categories of space that form the foundations of society and subjectivity in England and its colonies: domestic, shared/public, and agrarian. Throughout the thesis I argue for the material and ideological flow between these spaces as well as the discursive flow between the different genres of texts used to represent them. Equally, I argue for the flow between subject and space in the construction of normative or transgressive identities for both. I analyse a range of pamphlet, manuscript, and dramatic texts, seeing the flow of discourse and representational schemes between these genres as a key part of understanding the role of text in the construction of space and subjectivity. However, matters of genre are not disregarded, and I also argue for theatre’s unique role in synthesising and interrogating a wide range of spatial discourses emerging from England and its colonies. To frame my analyses of the relationships between subject, space, and text I draw on the work of Henri LeFebvre and Doreen Massey. I combine LeFebvre and Massey’s understanding of space as an ongoing socio-political process with recent work in embodied and distributed cognition in early modern studies, as exemplified by Mary Floyd Wilson and Garrett A. Sullivan Jr., that argues for a transactional relationship between subject and material environment. These approaches allow me to articulate the reflexive flow between the multiple material, textual, and ideological elements that construct subjectivity and space. In so doing this thesis (re)asserts the influence of early colonial discourse and practice on early modern English literature, and establishes the reflexive relationship between the spatial practices of England the New World.